Online Indonesian Islamist extremism : a gold mine of infomation - Nur Azlin Mohamed Yasin (2012)
Closing down Islamist extremist online sites may stem radicalisation in Indonesia. But the online phenomenon reflects an offline reality and is also a gold mine of information about extremist activities.